Competitiveness E-Commerce: An Empirical Study on MSMEs Producing Tempe Sanan Chips in Malang City - Chandra Mayasari; Ferry Prasetyia (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
This quantitative research was conducted to determine the effect of e-commerce adoption on the competitiveness of MSMEs in Tempe Sanan Chips Industry Center, Malang City. This study used primary data obtained from questionnaires distributed to respondents who were owners of the MSMEs in Sanan Tempe Chips Industry Center who had adopted e-commerce. This study used the Partial Least Square (PLS) method and employed SmartPLS 3.0 as a tool. The results of the analysis showed that the variable e-commerce adoption has a positive and significant effect on MSME competitiveness; the control variables human resources and business environment were found to have a positive and significant effect on e-commerce adoption; the control variables product innovation and product quality do not have a positive and significant effect on e-commerce adoption; the variables human resources, product innovation, and product quality do not have a significant effect on MSME competitiveness; and the control variable business environment has a significant positive effect on MSME competitiveness.